Influence of Human Leukocyte Antigen (HLA) Alleles and Killer Cell Immunoglobulin‐Like Receptors (KIR) Types on Heparin‐Induced Thrombocytopenia (HIT). Issue 9 (4th September 2017) - Karnes, Jason H.; Shaffer, Christian M.; Cronin, Robert; Bastarache, Lisa; Gaudieri, Silvana; James, Ian; Pavlos, Rebecca; Steiner, Heidi E.; Mosley, Jonathan D.; Mallal, Simon; Denny, Joshua C.; Phillips, Elizabeth J.; et al.
Abstract : Heparin‐induced thrombocytopenia (HIT) is an unpredictable, life‐threatening, immune‐mediated reaction to heparin. Variation in human leukocyte antigen (HLA) genes is now used to prevent immune‐mediated adverse drug reactions. Combinations of HLA alleles and killer cell immunoglobulin‐like receptors (KIR) are associated with multiple autoimmune diseases and infections. The objective of this study is to evaluate the association of HLA alleles and KIR types, alone or in the presence of different HLA ligands, with HIT. HIT cases and heparin‐exposed controls were identified in BioVU, an electronic health record coupled to a DNA biobank. HLA sequencing and KIR type imputation using Illumina OMNI‐Quad data were performed. Odds ratios for HLA alleles and KIR types and HLA*KIR interactions using conditional logistic regressions were determined in the overall population and by race/ethnicity. Analysis was restricted to KIR types and HLA alleles with a frequency greater than 0.01. The p values for HLA and KIR association were corrected by using a false discovery rate q<0.05 and HLA*KIR interactions were considered significant at p<0.05. Sixty‐five HIT cases and 350 matched controls were identified. No statistical differences in baseline characteristics were observed between cases and controls. The HLA‐DRB3*01:01 allele was significantly associated with HIT in the overall population (odds ratio 2.81 [1.57–5.02], p=2.1×10 −4, q=0.02) and in individuals with European ancestry, independent of other alleles. No KIR types were associated with HIT, although a significant interaction was observed between KIR2DS5 and the HLA‐C1 KIR binding group (p=0.03). The HLA‐DRB3*01:01 allele was identified as a potential risk factor for HIT. This class II HLA gene and allele represent biologically plausible candidates for influencing HIT pathogenesis. We found limited evidence of the role of KIR types in HIT pathogenesis. Replication and further study of the HLA‐DRB3*01:01 association is necessary.